Development of Fable Text Teaching Materials Based on Local Wisdom Values ​​for Middle School Students in Pematangsiantar for Indonesian Language Learning - Saragih, Victorya Dumaris; Lubis, Malan; Masniari, Surya (Jurnal Pendidikan Edutama, 2024)
The availability of teaching materials for tale texts including local wisdom remains restricted. This study intends to develop alternative teaching resources for character education through the use of learning technology. This is a development research project that will take place at SMP Negeri 4 Pematangsiantar City from January to May 2024. The study was carried out in stages, beginning with an analysis of the need for teaching materials with an educational component, followed by the collection, selection, and analysis of fable texts from the students' cultural surroundings that are suited to their psychological development. Data were gathered through interviews, observations, and document analysis. The data's validity is determined through expert examination. Data were analysed by content analysis. The research findings indicate that fable texts incorporating local wisdom might be employed as educational characters. Visually presenting open resources improves the function of character education for students